Development of a HPLC protocol to characterize flexible PU foams in support of advanced recycling - Jonas Cassimon; Marthe Nees; Matthew Porters; Cristina Moyaert; Muhammad Adeel; Valentino Fantozzi; Lukasz Pazdur; Christophe M.L. Vande Velde; Philippe Nimmegeers; Pieter Billen (Polymer Testing)
We present a novel High-Performance Liquid Chromatography (HPLC) protocol to characterize flexible polyurethane (PU) foams, aiming to enhance chemical recycling processes. The developed protocol consists of depolymerizing PU foam and analyzing the resultant mixture using HPLC. The developed HPLC method successfully separates the isocyanate derivatives, allowing for accurate quantification of both toluene diisocyanate (TDI) and methylene diphenyl diisocyanate (MDI) content. Additionally, the method identifies the formation of aromatic amines during depolymerization, serving as an indicator for urea bonds in the foam. Hydrolysis is used to estimate the isocyanate content of polymeric MDI foams, but this does not provide information on the urea content. Although polyol quantification was not yet achieved, the protocol determines the types, polarity, molecular weight, and distribution of polyols post-depolymerization using Gel Permeation Chromatography (GPC). This work provides a robust analytical framework for assessing PU foam waste streams, facilitating improved recycling and sustainability in PU applications.